Penerapan Model Pembelajaran Project Based Learning Berbantuan Media Canva untuk Meningkatkan Kemampuan Berpikir Kreatif - Afriki Teguh Prastyo; Soetarno Joyoatmojo; Mintasih Indriayu (Departement of Mathematics Education, 2024)
This study aims to analyze the effect of implementing project-based learning model assisted by Canva media on students' creative thinking skills. This research is a Classroom Action Research (CAR). The research was conducted over 2 cycles. Each cycle consists of planning, implementation, observation, and reflection activities. The subjects of this study were students of class X.E-3 SMA Negeri 2 Surakarta, totaling 36 students. Data collection techniques were observation, interview, and documentation. The results showed that by applying the project-based learning model assisted by Canva media can improve students' creative thinking skills. This can be seen from the percentage of the number of students with creative thinking skills in pre-action only 25% then after being given action in cycle 1 by applying the project-based learning model assisted by Canva media the percentage of students with creative thinking skills increased to 58.33%. After cycle 1, reflection and improvement were carried out which were then applied in cycle 2, the percentage of creative thinking skills increased to 77.78%. The conclusion of this study is that by applying the project-based learning model assisted by Canva media can improve the creative thinking skills of students in class X SMA Negeri 2 Surakarta.